Social studies in selected secondary schools in Ilorin Kwara State, Nigeria : a case study - Abdul Kabir, Asmau Imam (Institute of Education, International Islamic University Malaysia, 2013)
The purpose of education in Nigeria as in many other developing countries is the preparation of the individual to contribute to the development of the nation and for the transmission of the social and cultural values to new generations. Yet, the Nigerian society has been surrounded by a series of political, economic and social crises. For this reason, Social Studies is assigned the responsibility to develop in Nigerian youth an understanding of their societal values, knowledge, values and skills that would enable them to deal with and manage the forces of the world in which they live and learn how to live harmoniously in the society. Therefore, the aims of this study are to examine the contents and purposes of the Social Studies curriculum with special reference to its ability to instil high-quality moral values and good character in students and provide them the necessary skills, abilities and competencies which individual students require to participate in the development of the nation. The study explores the junior secondary schools' Social Studies curriculum in Ilorin, Kwara State by employing the methods and procedures of the qualitative research tradition. The techniques and qualitative inductive data analysis approaches were used to analyse all forms of data such as interview, classroom observation and analysis of related documents. The study employed the case study design and involved six teachers, ten students, a curriculum developer and a staff from the Kwara State Ministry of Education curriculum development unit. The study found that the Social Studies Curriculum in Nigeria is well structured and consists of the aims and objectives of the subject, appropriate selection of teaching aids, textbooks and techniques to be used to achieve the aims. It was also discovered that the Social Studies junior secondary school curriculum has content and teaching approaches that are suitable for students' moral development. However, it was noticed that the failure of government to supervise curriculum implementation, inadequate motivation given to teachers towards the curriculum, lack of material resources, insufficient time and teacher motivation towards the curriculum are hindering effective implementation of the curriculum in Kwara State junior secondary schools. Thus, the general finding of this research indicates that there is a mismatch between the designed curriculum and the implemented curriculum. The study recommends among others that the Social Studies curriculum should be reviewed and interactive programme in the form of teacher training, seminars, forums and workshops should be organised to familiarise teachers with the curriculum and to upgrade teachers' efficiency. This will enable them to acquire the pedagogical disposition for implementing the curriculum for students' moral development and eventually realizing the Nigerian society's ideals and values.